Selective engagement of long-latency reflexes in postural control through wobble board training - Theodore Deligiannis; Mahsa Barfi; Brian Schlattmann; Ken Kiyono; Damian G. Kelty-Stephen; Madhur Mangalam (Scientific Reports)
Abstract Long-latency reflexes (LLRs) are critical precursors to intricate postural coordination of muscular adaptations that sustain equilibrium following abrupt disturbances. Both disturbances and adaptive responses reflect excursions of postural control from quiescent Gaussian stability under a narrow bell curve, excursions beyond Gaussianity unfolding at many timescales. LLRs slow with age, accentuating the risk of falls and undermining dexterity, particularly in settings with concurrent additional tasks. We investigated whether the wobble board could cultivate the engagement of LLRs selectively in healthy young participants executing a suprapostural Trail Making Task (TMT). A concurrent additional-task demand constituted visual precision predominantly along the anteroposterior (AP) axis and mechanical instability mainly along the mediolateral (ML) axis. We scrutinized planar center-of-pressure (CoP) trajectories to quantify postural non-Gaussianity across various temporal scales. Wobble board increased engagement of LLRs and decreased engagement of compensatory postural adjustments (CPAs), indicated by the peak in non-Gaussianity of CoP planar displacements over LLR-specific timescales (50–100 ms) and non-Gaussianity of CoP planar displacements progressively diminishing over CPA-specific timescales ( $$>100$$ ms). Engagement with TMT did not show any noticeable influence on non-Gaussian postural sway patterns. Despite aligning the unstable axis of the wobble board with participants’ ML axis, thus rendering posture more unstable along the ML axis, the wobble board increased engagement of LLRs significantly more along the AP axis and reduced engagement of CPAs significantly more along the ML axis. These findings offer initial mechanistic insights into how wobble boards may bolster balance and potentially reduce the occurrence of falls by catalyzing the engagement of LLRs selectively.